(untitled) (Journal of Health, Population and Nutrition, 2014)
This study aimed to validate a questionnaire on dietary fibre (DF)-related knowledge in a Turkish student population. Participants (n=360) were either undergraduate students who have taken a nutrition course for 14 weeks (n=174) or those in another group who have not taken such a nutrition course (n=186). Testretest reliability, internal reliability, and construct validity of the questionnaire were determined. Overall internal reliability (Cronbachs alpha=0.90) and test-retest reliability (0.90) were high. Significant differences (p<0.001) between the scores of the two groups of students indicated that the questionnaire had satisfactory construct validity. It was found that one-fifth of the students were unsure of the correct answer for any item, and 52.5% of them were not aware that DF had to be consumed on a daily basis. Only 36.4 to 44.2% of the students were able to correctly identify the food sources of DF. DOI: http://dx.doi.org/10.3329/jhpn.v31i4.20048 J HEALTH POPUL NUTR 2013 Dec; 31(4): 497-503